Analisis Risiko Kerja Pada Sudin Penanggulangan Kebakaran Dan Penyelamatan Kota Administrasi Jakarta Utara - Teguh Santoso; Difa Agustiawan (Jurnal Ilmu Administrasi Publik, 2023)
This research is motivated by the phenomenon that the number of human resources is still minimal, facilities and infrastructure are still inadequate, coordination with related agencies is still a lot of obstacles. This study aims to find out and analyze the work risks in the North Jakarta Administrative City Fire Fighting and Rescue Sub-Department. To analyze the obstacles in the work risk in the North Jakarta Administrative City Fire Management and Rescue Sub-Department. To analyze the efforts made in the Work Risk at the North Jakarta Administrative City Fire Management and Rescue Sub-Department. In answering this problem the author uses descriptive qualitative research, data is collected by describing, summarizing various conditions, situations or social phenomena that exist in society and efforts to draw that reality to the surface as characteristics, characteristics, traits, models, signs or descriptions of conditions, situations or certain phenomena and data analysis was carried out by conducting in-depth interviews with informants. While the data analysis technique uses a qualitative descriptive statistical approach. The criteria for informants that the authors make as informants in this study are those who control and understand the conditions of the research object, who are involved or occupy positions related to the topic under study and have enough time, namely taking data that is appropriate to the research context and ignoring data that is not needed. The results of the work risk research at the North Jakarta Administrative City Fire and Rescue Sub-agency based on the results of interviews still have problems occurring.